1, 4‐Dihydroxy‐2‐naphthoic acid from Propionibacterium freudenreichii reduces inflammation in interleukin‐10‐deficient mice with colitis by suppressing macrophage‐derived proinflammatory cytokines. Issue 3 (25th June 2013) - Okada, Yoshikiyo; Tsuzuki, Yoshikazu; Narimatsu, Kazuyuki; Sato, Hirokazu; Ueda, Toshihide; Hozumi, Hideaki; Sato, Shingo; Hokari, Ryota; Kurihara, Chie; Komoto, Shunsuke; Watanabe, Chikako; Tomita, Kengo; et al.
Abstract : DHNA derived from Propionibacterium freudenreichii attenuates colonic inflammation by a direct action on macrophages, leading to decreased production of proinflammatory cytokines. Abstract : The anti‐inflammatory mechanism of prebiotics has recently been shown to have an impact on the host immune system. DHNA from Propionibacterium freudenreichii is known to promote the proliferation of Bifidobacterium and can ameliorate colitis, although its mode of action remains unknown. In this study, we investigated whether DHNA attenuates inflammation in piroxicam‐treated IL‐10 −/− mice, particularly focusing on the changes of the host immune mechanism. DHNA was administered to IL‐10 −/− mice with colitis, and the expression of adhesion molecules and mRNA levels of proinflammatory cytokines were determined. DHNA pretreatment attenuated the piroxicam‐induced histological changes. The increased F4/80‐positive cell infiltration and VCAM‐1 expression were decreased by DHNA administration. The increased mRNA levels of proinflammatory cytokines were also suppressed by DHNA. In in vitro experiments, increased mRNA levels of proinflammatory cytokines after endotoxin exposure were decreased significantly by DHNA pretreatment in RAW264.7, a macrophage cell line, and IL‐10 −/− mice BMMs, whereas the expression of VCAM‐1 in bEnd.3 cells, a endothelial cell line, was not affected. Taken together, these findings suggest that administration of DHNA is useful for the treatment of colitis in piroxicam‐treated IL‐10 −/− mice and that attenuation of colitis by DHNA may partly be a result of its direct action on intestinal macrophages to inhibit proinflammatory cytokine production.